7. Improving Learners' Writing Skills and Language Awareness via Contrastive Analysis (Journal of Educational Sciences, 2025)
In foreign language instruction, the dynamics between educators and learners, along with linguistic and emotional factors, significantly influence the effective teaching of the target language. It is recognized that the linguistic variable, particularly the native language, influences students' writing performances during the instruction of Turkish to Kazakh learners. It has been observed that Kazakh students typically exhibit mistakes in their written expressions that are rooted in their mother tongue. Contrastive analysis is a method that increases the acquisition of the target language by focusing on interlingual linguistic aspects and emerges as a solution to these issues. This study examined the impact of the contrastive analysis on Kazakh students' writing performance and the development of linguistic consciousness. A mixed method design combining quasi-experimental and focus group interview methods was used to achieve the study's goal. The research group consists of Kazakh A2-level students studying Turkish as a foreign language at Abai Kazakh National Pedagogical University. The quantitative design of the study involved 66 students, whereas the qualitative design included 20 students in the focus group. The writing component of the Turkish Proficiency Test and a semi-structured interview form were utilized to collect data. The study's findings were analyzed using SPSS 23 and the MaxQDA 24 programs. The study's findings demonstrated that the contrastive analysis improved students' writing performance, and the combined effect of group and measurement was significant. Furthermore, the related method enhanced students' language awareness, awareness of mistakes, ability to monitor the writing process, and knowledge of interlingual vocabulary and grammar. Additionally, students had positive attitudes regarding this method. These findings are essential for creating teaching materials using the right process and transforming the curriculum.Key words: Contrastive analysis method, writing skills, language awareness, teaching Turkish to Kazakh students, mother tongue.